Utilization of Educational Technology in The Learning Process in The Sub-District of Tebas, Sambas Regency - Warneri; Okianna (JTP - Jurnal Teknologi Pendidikan, 2022)
This study aims to determine the use of educational technology in the learning process for educators in Tebas District, Sambas Regency, the theoretical use of research to contribute to the development and use of educational technology and practically to be able to apply the development of educational technology today. The variables in this study are Utilization of educational technology in the learning process" with indicators of learning models, learning strategies, learning methods, learning media and learning outcomes. The research method uses descriptive verification method in the form of case study research. The results of the study showed that the models, strategies, methods and learning media as well as learning resources most of the educators had mastered and could be applied, and it should be noted that the facilities and infrastructure that can support the use of educational technology such as internet facilities, wifi and equipment to support the implementation of learning when they want to implementing educational technology in delivering lesson messages and the lack of availability of learning resources in supporting the smooth process of using technology other than the teacher concerned.